Epiphytic Plants of Citrus in Florida - Ramdas Kanissery; Mongi Zekri (EDIS, 2017)
Epiphytes are a group of plants that grow on citrus by using the trees for anchorage and support. These plants are not in direct contact with the ground and obtain moisture and nutrients from the air and rainfall.  Even though directly harmless to the citrus trees, excessive growth of epiphytes may be a problem as they result in competition for sunlight, inhibition of growth, and may obstruct the harvesting and chemical spraying. Physical removal and copper sprays are effective measures to eradicate epiphytes from the citrus trees.